Factors associated with a measles outbreak in children admitted at Mahosot Hospital, Vientiane, Laos - Douangdala Phouvieng; Keomany Sommay; Vorasane Banlieng; Phounesavath Khamphouvanh; Souvannasing Phoutthalavanh; Khomthilat Tiengthong; Mayxay Mayfong; Philavong Khamseng; Srour Leila; Newton Paul N (BMC, 2007)
Abstract Background In 2002 and 2003 there were large outbreaks of measles in many provinces of Laos, including in Vientiane. We therefore conducted a study to determine risk factors associated with measles amongst children admitted at Mahosot Hospital, Vientiane. Methods A retrospective case-control study was conducted in 50 children with clinical measles who were matched by age and sex with 50 healthy children (who had never had a febrile rash) living in the same villages as the cases. Results The proportion of children with complete immunizations was significantly lower in the group with clinical measles compared to the controls [13/50 (26%) vs 34/50 (68%), P < 0.001). The percentage of children who had received measles vaccine at 9-23 months of age was significantly lower in the group with clinical measles compared to the healthy controls [12/50 (24%) vs 24/50 (48%), P = 0.01). The family educational and socio-economic status did not differ significantly (P > 0.05) between cases and controls. Conclusion These results emphasize the importance of intensification of measles immunization coverage in Laos. The strengthening of campaigns with large, widespread high second dose coverage is likely to be a key measure to prevent further measles outbreaks in Laos (192 words).